2015
DOI: 10.1002/ejlt.201500283
|View full text |Cite
|
Sign up to set email alerts
|

Adding talc particles improves physical properties of palm oil‐based shortening

Abstract: This paper reports the effects of adding talc particles on the physical properties of palm oil (PO)‐based shortening formed by working refined PO (RPO) after rapid cooling. We examined the thermal and viscoelastic behavior of RPO in bulk fat systems, and the polymorphism and hardness of the shortening in the presence and absence of talc particles. In addition, the microstructure of fat crystals formed was observed. The effects of talc addition are summarized as follows: (i) When RPO was cooled at a rate of 5°C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 32 publications
0
19
1
Order By: Relevance
“…The second (i.e., T m = 32.0 AE 1.7 C) and third (i.e., T m = 36.9 AE 1.5 C) endotherms remained convoluted, regardless of dispersion or shear speed. The literature has suggested that β' crystals of POP, PPO, and PPP appear within this range, however, it should be noted that these studies cooled their systems to temperatures far below 20 C (Bayés-García et al, 2015;Minato et al, 1997;Yoshikawa et al, 2016). Finally, the fourth endotherm (i.e., T m = 43.2 AE 0.7 C) appeared to be most separated from the other endotherms and was completely removed from the thermal profile as both dispersion concentration and shear speed increased.…”
Section: Palm Oil Crystal Identification Via Tag Standardsmentioning
confidence: 89%
See 3 more Smart Citations
“…The second (i.e., T m = 32.0 AE 1.7 C) and third (i.e., T m = 36.9 AE 1.5 C) endotherms remained convoluted, regardless of dispersion or shear speed. The literature has suggested that β' crystals of POP, PPO, and PPP appear within this range, however, it should be noted that these studies cooled their systems to temperatures far below 20 C (Bayés-García et al, 2015;Minato et al, 1997;Yoshikawa et al, 2016). Finally, the fourth endotherm (i.e., T m = 43.2 AE 0.7 C) appeared to be most separated from the other endotherms and was completely removed from the thermal profile as both dispersion concentration and shear speed increased.…”
Section: Palm Oil Crystal Identification Via Tag Standardsmentioning
confidence: 89%
“…Finally, the fourth endotherm (i.e., T m = 43.2 AE 0.7 C) appeared to be most separated from the other endotherms and was completely removed from the thermal profile as both dispersion concentration and shear speed increased. This peak has been most commonly associated with β crystals (Braipson-Danthine and Gibon, 2007;Che Man et al, 1999) and, more specifically, PPP β crystals (Yoshikawa et al, 2016).…”
Section: Palm Oil Crystal Identification Via Tag Standardsmentioning
confidence: 97%
See 2 more Smart Citations
“…The crystallization behavior of oils with high melting points, such as palm oil and cacao butter, has been investigated as well as the effect of adding other oils and fats or talc (de Oliveira et al, 2015;Quast et al, 2013;Yoshikawa et al, 2016). The crystallization behavior of vegetable oils with low melting points, sunflower (Calligaris et al, 2008) and olive oils (Barba et al, 2013;Bayés-García et al, 2017), has also been investigated.…”
Section: Introductionmentioning
confidence: 99%